Laser-welded butt joints of Ti2AlNb/42CrMo steel with addition of V interlayer - Jie Ning; Long-Zheng Pan; Lin-Jie Zhang (Journal of Materials Research and Technology, 2024)
Welding Ti2AlNb and 42CrMo steel is important in the field of materials engineering. The formation of Ti–Fe intermetallic compounds upon melting makes it a challenging task due to the significant disparities in the physical properties and chemical compositions of these two materials. An orthogonal experiment was designed and conducted, and crack-free laser-welded butt joints of Ti2AlNb/42CrMo steel were achieved under optimized parameters. The joints exhibited a tensile strength of approximately 162 MPa. Fracture surface analysis revealed substantial amounts of Fe2Ti and FeTi intermetallic compounds within the weld zone. According to the principle of element compatibility, a method is proposed for incorporating a partially melted V interlayer for laser butt welding of Ti2AlNb/V/42CrMo steel. The laser beam was vertically incident on the interface between Ti2AlNb and V, as well as the interface between V and steel. No visible microcracks were observed after welding. Elemental analysis results indicated that the V interlayer prevented the formation of the Fe–Ti mixed zone. Furthermore, the weld zone primarily consisted of (Fe, V) solid solution and (β-Ti, V) solid solution; thus, Ti–Fe intermetallic compounds were not formed. The tensile strength of the joint reached 572 MPa, and the joint fractured within the unmelted V layer, exhibiting a typical ductile fracture morphology.